Assessment of Tolerability and Safety of Monocomponent Complementary Food Products in the Diet of Infants With Risk for Allergic Diseases - L. S. Namazova-Baranova; T. V. Turti; M. A. Snovskaya; O. L. Lukoyanova; Ye. P. Zimina; Ye. A. Bakovich; Z. F. Zokirova; A. A. Gorbachyova ("Paediatrician" Publishers LLC, 2016)
Background: Children with burdened allergological history and/or having preliminary allergy manifestations need the effective prevention of allergy from the first months of life.Objective: Our aim was to assess the tolerability, safety, and efficacy of monocomponent complementary food products in the diet of infants with high risk for allergic diseases.Methods: Tolerability, safety, and efficacy of monocomponent complementary food products (vegetable puree, fruit juices, and after 6 months - meat sauce) were studied in a singlecentre, prospective, comparative study. The symptoms of indigestion, skin allergy symptoms were registered, the results of coprological research and immunogenicity of complementary food products were assessed.Results: The study included 200 children in the age from 5 months from the risk group of allergy developing. Children were divided into 4 groups of 50 people. It was found that complementary food products were well tolerated and assimilated by children, did not cause skin and gastrointestinal allergic reactions in healthy children with risk of allergy developing. Food antigens of complementary food components (pumpkin, rabbit meat, turkey meat, apples, pears, plums) were characterized by low immunogenicity: the level of specific IgE to the specified products did not change in blood serum and remained at a low level at the beginning and at the end of the study (ranging from 0.01 to 0.03 kE/l).Conclusion: Studied complementary food products (vegetable-, fruit- and meat-based) can be used in the diet of children with high risk for allergy.